Digest: The role of intra‐ and interspecific behavior in habitat use evolution. (6th January 2020) - Zak, Vanessa
Abstract: Cycloramphus and Zachaenus Neotropical frogs breed in rocky streams (saxicolous breeding) or in terrestrial environments. In their recent work, de Sá et al. investigate shifts between these habitats and the impact that these shifts have on body size and sexual size dimorphism (SSD). The researchers found that terrestrial breeding evolved on three occasions. Additionally, there was an association between habitat and SSD, with decreases in male body size correlating with shifts toward terrestrial breeding.